What determines utility of international currencies? - Eiji Ogawa; Makoto Muto (Journal of Risk and Financial Management, 2019)
In previous studies, we estimated a time series of coefficients on five international currencies (the US dollar, the euro, the Japanese yen, the British pound, and the Swiss franc) in a utility function. We call the coefficients utilities of international currencies. The time series show that the utility of the US dollar as an international currency has remained in the first position in the changing international monetary system despite of the fact that the euro was created as a single common currency for European countries. On one hand, the utility of the Japanese yen has been declining as an international currency. In this paper, we investigate what determines the utility of international currencies. We use a dynamic panel data model to analyze the issue with Generalized Method of Moments (GMM). Specifically, liquidity shortage in terms of an international currency means that it is inconvenient for economic agents to use the relevant currency for international economic transactions. In other words, liquidity shortages might reduce the utility of an international currency. In this analysis we focus on liquidity premium which represents a liquidity shortage in terms of an international currency. Our empirical results showed not only inertia in terms of change but also the impact of a liquidity shortage in an international currency on the utility of the relevant international currency.
Keywords: 330; utility of international currency; inertia; liquidity risk premium; US dollar; Japanese yen